Victim as a relative status - Marshall, Hannah (Theoretical criminology, 2024)
This article advances a theory of the ‘relative’ nature of victim status, demonstrating that whether an individual is identified as a victim is, in part, conditional on their relationships with others. Using the example of victim identification in cases of child criminal exploitation, this article demonstrates that youth justice practitioners’ perceptions of young people's peer relationships and their relationships with their families had a significant impact on whether young people were identified as victims of child criminal exploitation. To explain this dynamic, this article then further explores the conceptual nature of victim status, focusing on its transient and finite qualities. In doing so, this article begins to address the relational gap in the study of processes of victim identification.